PUBLIC SMOKING ISSUE - NOVEMBER 1986 REPORT - Stuntz, S.; Ross, J. (Tufts Archival Research Center, 2007)
Confidential; Memo to Peter Sparber from Susan Stuntz and Jeff Ross reporting on the public smoking issue in November 1986. Provides and overview and highlights. Lists issues still in need of attention. Outlines monthly progress towards plans, listing goals, tactics, and strategies.